Respuesta :

Answer:

[tex]{ \tt{( \frac{ - 4}{9} \times \frac{63}{28}) - ( \frac{33}{66} \times \frac{ - 51}{17} ) + ( \frac{5}{8} \times \frac{4}{10)} }} \\ \\ = { \tt{( \frac{ - 4}{28} \times \frac{63}{9}) - ( \frac{1}{2} \times \frac{ - 3}{1} ) + ( \frac{5}{10} \times \frac{4}{8} )}} \\ \\ { \tt{ = ( - 1) - ( - \frac{3}{2} ) + ( \frac{1}{4}) }} \\ \\ = { \tt{ \frac{3}{4} }}[/tex]

Answer:

[tex]\sf \dfrac{3}{4}[/tex]

Step-by-step explanation:

Given expression:

[tex]\implies \sf \left(\dfrac{-4}{9} \times \dfrac{63}{28}\right)-\left(\dfrac{33}{66} \times \dfrac{-51}{17}\right)+\left(\dfrac{5}{8} \times \dfrac{4}{10}\right)[/tex]

[tex]\textsf{Apply the fraction rule} \quad \dfrac{a}{b} \times \dfrac{c}{d}=\dfrac{a \times b}{c \times d}:[/tex]

[tex]\implies \sf \left(\dfrac{-4\times63}{9\times28} \right)-\left(\dfrac{33 \times -51}{66 \times 17}\right)+\left(\dfrac{5\times4}{8\times10} \right)[/tex]

Multiply the numbers:

[tex]\implies \sf \left(\dfrac{-252}{252} \right)-\left(\dfrac{-1683}{1122}\right)+\left(\dfrac{20}{80} \right)[/tex]

Reduce the fractions:

[tex]\implies \sf -1-\left(\dfrac{-3}{2}\right)+\left(\dfrac{1}{4} \right)[/tex]

[tex]\textsf{Apply rule}\quad \:a-\left(-b\right)=a+b:[/tex]

[tex]\implies \sf -1+\dfrac{3}{2}+\dfrac{1}{4}[/tex]

Adjust the fractions based on the LCM of 4:

[tex]\implies \sf \dfrac{-4}{4}+\dfrac{6}{4}+\dfrac{1}{4}[/tex]

[tex]\textsf{Apply the fraction rule} \quad \dfrac{a}{c}+\dfrac{b}{c}=\dfrac{a+b}{c}:[/tex]

[tex]\implies \sf\dfrac{-4+6+1}{4}[/tex]

Add the numbers in the numerator:

[tex]\implies \sf \dfrac{3}{4}[/tex]